What do the teachers want? A targeted needs assessment survey for prospective didactic training of psychiatry medical educators - Baessler, Franziska; Zafar, Ali; Koelkebeck, Katja; Frodl, Thomas; Signerski-Krieger, Jörg; Pinilla, Severin; Barth, Gottfried M.; Jannowitz, Deborah; Speerforck, Sven; Roesch-Ely, Daniela; Kluge, Ina; Aust, Miriam; et al. (GMS Journal for Medical Education, 2024)
Objectives: Physicians and psychologists at psychiatric university hospitals are assigned teaching tasks from the first day of work without necessarily having the prerequisite training in teaching methods. This exploratory survey provides a needs-based analysis for the prospective didactic training of physicians and psychologists at psychiatric hospitals in Germany, Austria and Switzerland. Methods: An online questionnaire was distributed at medical schools via email in German-speaking countries in Europe. All physicians involved in teaching medical students at psychiatry faculties were eligible to participate in the survey. Participants were further requested to recruit eligible participants (snowball sampling). Responses were analyzed descriptively, and differences between groups were calculated using nonparametric Mann-Whitney U tests (p<.05). Results: Overall, 97 respondents (male=55, female=42; mean age= 40.6) from 19 medical schools completed the survey. The respondents consisted of 43 residents, 39 specialists, 6 chief physicians and 9 psychologists. Of the respondents, 97.6% rated didactic competence as either highly relevant or rather relevant for teaching medical students. The highest overall interest was shown for bedside teaching (mode=4; IQR: 2-4) and error culture (mode=3; IQR: 2-4). Respondents expressed the highest training needs for topics regarding presentation and communication (mode=3; IQR: 2-3). Resident physicians were significantly more interested in bedside teaching (U=362.0, p=0.004) and roleplay (U=425.0; p=0.036) than specialist physicians, who were more inter-ested in examination didactics (U=415.0; p=0.022). Chief physicians displayed significantly deeper interest in group dynamics (U=51; p=0.023) than specialist physicians. In-person training was preferred by a majority of respondents, and 27.4% preferred online/web-based training. Conclusions: The majority of physicians and psychologists at psychiatric university hospitals considered professional development for faculty to be helpful for teaching medical students. Bedside teaching and error culture management were the most desired teaching topics for training medical teachers. Tailored educational interventions are recommended, with target-oriented priorities for different hierarchical levels.
CRIS-Team Scopus Importer:2024-05-10
Keywords: didactics; medical curriculum; medical education; medical teaching; psychiatric education; psychiatry; train the trainers